2008
DOI: 10.1017/s0007485308006093
|View full text |Cite
|
Sign up to set email alerts
|

Quackgrass- and ryegrass-adapted populations of the cereal rust mite, Abacarus hystrix (Acari: Eriophyidae), differ in their potential for wheat, Triticum aestivum, colonization

Abstract: The cereal rust mite, Abacarus hystrix, is one of the most notable among mites causing losses in cultivated grasslands. It is one of a few eriophyoid species for which a broad host range has been reported. Recent studies, however, have shown that host specialization is very likely in this species. For two populations of A. hystrix (one inhabiting perennial ryegrass, the second inhabiting quackgrass), host-associated differences correlated with strong host fidelity, distinct phenotypes and reproductive barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Morphometric analyses thus provide a reasonable option with balance in effectiveness and efficiency. The present and many previous studies have proved morphometrics a useful tool in eriophyoid classification (Huang et al 1996; Magud et al 2007; Skoracka et al 2002; Navia et al 2006, 2009; Skoracka 2009a, b). …”
Section: Resultssupporting
confidence: 51%
“…Morphometric analyses thus provide a reasonable option with balance in effectiveness and efficiency. The present and many previous studies have proved morphometrics a useful tool in eriophyoid classification (Huang et al 1996; Magud et al 2007; Skoracka et al 2002; Navia et al 2006, 2009; Skoracka 2009a, b). …”
Section: Resultssupporting
confidence: 51%
“…Three samples (AH10, AH20 and AH30) originated from females that were reared as laboratory colonies previously used in cross-breeding and colonization experiments (e.g. Skoracka, 2008Skoracka, , 2009 where the details regarding rearing mites are described). The distances between collecting sites ranged from 1.5 to 105.5 km.…”
Section: Mite Samplingmentioning
confidence: 99%
“…Edwards & Labhart, 2000; Drés & Mallet, 2002). The latter phenomenon seems to be more likely in respect to the cereal rust mite since it has been demonstrated that two populations of this mite (quackgrass- and ryegrass-associated) differ in host preferences and performance (Skoracka & Kuczyński, 2006; Skoracka et al , 2007) and have different physiological host ranges (Skoracka, 2009). Thus, these two populations of A. hystrix were concluded to be highly host-adapted.…”
Section: Introductionmentioning
confidence: 99%
“…In our samples, we found several animal, fungal, and bacterial taxa that are of agricultural and medical importance to humans (Supporting Information 3), which highlights a range of possible uses of eDNA from spider webs. Notable examples among plant pathogens and disease‐causing agents are genera that include grain rust and wheat curl mites (Eriophyidae; Hartford et al, 1982; Skoracka, 2009), gall and fungus gnats (Cecidomyiidae, Sciaridae; Gagné, 2004; Scheepmaker et al, 1997), aphids (e.g., Pineus and Anoecia ; Day et al, 2003; McGaving, 1993; van Emden & Harrington, 2017), several fungal representatives that damage wheat crops (e.g., Fusarium and Ustilago ; Andrade et al, 1994; Kämper et al, 2006; Nelson et al, 1994), eudicot plants ( Verticillium ; Barbara & Clewes, 2003), and rice ( Magnaporthe grisea ; Talbot, 2003), as well as several bacterial genera that include plant pathogenic representatives, such as Pseudomonas , Erwinia , Dickea and Pectobacterium (Mansfield et al, 2012). Therefore, spider web eDNA could be used for early detection of agricultural pests, even in the absence of disease symptoms, an approach already demonstrated for eDNA from orchards (Guarnaccia et al, 2017; Nicolaisen et al, 2017; Valentin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%